2005
DOI: 10.1159/000089409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lithium on Endolymph Homeostasis and Experimentally Induced Endolymphatic Hydrops

Abstract: There is evidence to suggest that water homeostasis in the inner ear is regulated via the vasopressin (VP)-aquaporin 2 (AQP2) system in the same fashion as in the kidney. The VP-AQP2 system in the kidney is well known to be inhibited by lithium, resulting in polyuria due to a decrease in reabsorption of water in the collecting duct of the kidney. Therefore, lithium is also likely to inhibit the VP-AQP2 system in the inner ear, and consequently exert some influence on inner ear fluid homeostasis. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Previous studies have shown that AQP2 protein and/or mRNA are expressed in the inner ear of rats. 19,39,46 Furthermore, the V2 receptor and/or its mRNA are found in the cochlea. 16,18 These previous studies suggest that water homeostasis in the inner ear is partly regulated via the VP-AQP2 system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that AQP2 protein and/or mRNA are expressed in the inner ear of rats. 19,39,46 Furthermore, the V2 receptor and/or its mRNA are found in the cochlea. 16,18 These previous studies suggest that water homeostasis in the inner ear is partly regulated via the VP-AQP2 system.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that the stria vascularis, which was a possible site of the production of endolymph, showed no AQP2 immunoreactivity. On the other hand, our recent histochemical studies [11,13,27] revealed that AQP2 proteins were clearly expressed in the rat stria vascularis and the rat/human endolymphatic sac ( fig. 5 ).…”
Section: Hormonal Aspects Of MD On the Basis Of Experimental Studiesmentioning
confidence: 99%
“…8 ). Decompression of the endolymphatic space was also produced by the application of lithium, one of the VP-AQP2 system inhibitors [27] . These experimental results could open up possibilities for new therapeutic methods for MD.…”
Section: Hormonal Aspects Of MD On the Basis Of Clinical And Experimementioning
confidence: 99%
“…Previously, we reported that the plasma antidiuretic hormone (p-ADH) level is increased in patients with ELH [5] . In an experimental study, we reported that chronic administration of ADH induced ELH in guinea pigs [6] , and that aquaporin-2 (AQP2), an ADH-dependent water channel in the stria vascularis and the endolymphatic sac in the rat inner ear, was controlled by ADH [7,8] . Therefore, measurement of p-ADH seems useful as a test to confirm suspected ELH.…”
Section: Introductionmentioning
confidence: 99%